Chemistry of Materials and Energy. Examples and Future of a Millennial Science - Jean-Marie Tarascon (Collège de France, 2017)
Since Antiquity, humans have used processes to transform the materials of their environment to suit their needs. Solid-state chemistry, initially a series of recipes, became a real science of matter and its transformations following nineteenth-century scientific discoveries. It is now used to develop efficient and eco-compatible materials to transport or store energy. Solid-state chemistry thus plays a crucial role in finding the answers that science will have to bring to humanity's new conce...